Cardio‐geriatric model of care in acute heart failure: initial experience of a multidisciplinary approach in complex elderly patients. Issue 4 (8th April 2020) - Mulligan, Andrew; Seman, Michael; Abramowski, Rebecca; Falls, Roman; Scholes, Elizabeth; Vogrin, Sara; Long, Claire; Cox, Nicholas; Neil, Christopher J.
Abstract: A 'cardio‐geriatric' heart failure model of care was implemented to address the high rates of readmission in elderly acute decompensated heart failure patients. Despite demonstrably intensified management in both the cardiology and geriatric domains, this study did not demonstrate a positive effect on the primary outcome of all cause readmissions at 30 days.